Method for preparing composite solid electrolyte by initiator adsorption carrier based on nanostructure
By forming a PLiMA cladding layer on the surface of the inorganic nanolithium ion conductor and evenly distributing the electrolyte material during the in-situ curing process, the problem of battery performance degradation caused by high impedance of the solid-solid interface is solved, and the improvement of battery performance and stability is achieved.
Patent Information
- Application Number
- CN202411604788.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The high impedance of the solid-solid interface will affect the ionic conductivity of lithium-ion batteries, resulting in a decrease in charge and discharge performance and rate performance.
The method of preparing composite solid electrolytes based on nanostructures is adopted to form a PLiMA cladding layer on the surface of the inorganic nanolithium ion conductor, and the release rate of the initiator is controlled and the electrolyte material is evenly distributed during the in situ curing process.
The electrochemical performance and cyclic performance of the composite electrolyte are improved, the performance and stability of the battery are enhanced, and the overall lithium ion concentration and conductivity are increased.
Smart Images

Figure BDA0005129260210000091
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a method for preparing a composite solid electrolyte based on a nanostructured initiator adsorption carrier. Background Art
[0002] Lithium-ion batteries have been widely used in digital products and new energy vehicles due to their high energy density and low self-discharge rate. However, most current lithium-ion batteries use organic liquid electrolytes, and their energy density is close to a bottleneck. In extreme cases such as puncture or short circuit, they are prone to fire and explosion accidents. Therefore, it has become an urgent need to design and develop high-performance electrolytes to improve the safety and electrochemical performance of lithium-ion batteries.
[0003] Compared with traditional organic electrolytes, solid electrolytes significantly improve the safety performance of batteries because they reduce the flammable components in the battery. However, the high impedance of the solid-solid interface will affect the ionic conductivity of the battery, which will lead to a decrease in the charge and discharge performance and rate performance. To this end, the solid electrolyte is set on the surface of the electrode by in-situ curing. The solid electrolyte prepared by in-situ curing reaction can effectively improve the interface compatibility between the electrolyte and the electrode, simplify the battery assembly process, and reduce manufacturing costs.
[0004] Polymer electrolytes are expected to be used to build high-safety solid-state batteries due to their high flexibility and good processability. However, the low ionic conductivity and ion migration number of polymer electrolytes limit the fast charge and discharge performance of solid-state batteries. In particular, electrolytes prepared by solution casting use a large amount of organic solvents, which leads to problems such as solvent residue and poor interface contact. To this end, a method for preparing a composite solid electrolyte based on a nanostructured initiator adsorption carrier was developed. Summary of the invention
[0005] The present application provides a method for preparing a composite solid electrolyte based on a nanostructured initiator adsorption carrier to solve the problem that the high impedance of the solid-solid interface will affect the ionic conductivity of the battery, thereby causing a decrease in the charge and discharge performance and rate performance. The method can directly provide a lithium ion source. Since PLiMA carries its own lithium ions, it can increase the overall lithium ion concentration and conductivity.
[0006] The present application provides a composite solid electrolyte prepared based on a nanostructured initiator adsorption carrier. The raw material components for preparing the composite solid electrolyte include, by weight, 20-40 parts of a small molecule polymer monomer, 1-4 parts of an initiator, 2-6 parts of a lithium salt, 3-9 parts of an inorganic nanostructured lithium ion conductor, and 10-20 parts of an organic solvent.
[0007] Preferably, the polymerizable monomer includes any one or a combination of at least two of acrylic acid, methacrylic acid, methyl methacrylate, pentaerythritol tetraacrylate, pentaerythritol triacrylate, acrylonitrile, ethylene carbonate, ethylene oxide or 1,3-dioxolane.
[0008] Preferably, the initiator includes any one of azobisisobutyronitrile, azobisisoheptanenitrile, azoisobutylcyanoformamide, dimethyl azobisisobutyrate, dicumyl peroxide or dibenzoyl peroxide, or a combination of at least two thereof.
[0009] Preferably, the lithium salt includes any one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(difluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium bis(oxalatoborate), lithium difluorooxalatoborate or lithium bis(oxalatoborate), or a combination of at least two thereof.
[0010] Preferably, 1-3 parts of additives are also included, and the additives include any one or a combination of at least two of vinylene carbonate, fluoroethylene carbonate, propylene sulfite, ethylene sulfate, fluorobenzene or sodium dodecyl sulfate.
[0011] Preferably, the particle size of the inorganic nanostructured lithium ion conductor is 10nm-500nm; the inorganic nanostructured lithium ion conductor includes at least one of Li0.5La0.5TiO3, lithium nitrate, lithium fluoride, trilithium phosphate, and lithium niobate.
[0012] Preferably, the organic solvent includes any one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl formate, dimethoxymethane or acetonitrile, or a combination of at least two thereof.
[0013] Preferably, a method for preparing a composite solid electrolyte based on a nanostructured initiator adsorption carrier comprises the following steps:
[0014] A. First, dissolve the initiator in a small amount of anhydrous ethanol, stir evenly and add the inorganic nano lithium ion conductor Li 1.3 Al 0.3 Ti 1.7 (PO4)3 powder, ultrasonically disperse for 30-40 minutes, and then stir at a low speed for 4-5 hours to allow the initiator to be uniformly adsorbed on the surface of the inorganic lithium ion conductor;
[0015] B. drying the mixture under vacuum conditions to remove ethanol, thereby obtaining an inorganic lithium ion conductor material adsorbed with an initiator;
[0016] C. Then, PLiMA is dissolved in chloroform at a mass ratio of 1:10, and the inorganic lithium ion conductor adsorbed with the initiator is added to the solution, ultrasonically dispersed for 30-40 minutes, and stirred at a low speed for 3-4 hours to ensure that PLiMA is evenly coated on the surface of the inorganic lithium ion conductor;
[0017] D. vacuum drying the mixture to remove chloroform, thereby obtaining an inorganic lithium ion conductor material with PLiMA coated on the surface;
[0018] E. Next, a small molecule polymerization monomer, an initiator, a lithium salt, an organic solvent, and an inorganic lithium ion conductor material coated with PLiMA are mixed in an argon atmosphere glove box to obtain an in-situ solidified electrolyte precursor;
[0019] F. Inject the in-situ solidified electrolyte precursor into the battery cell, let it stand for 1 minute under a vacuum of -80 kPa, and let it stand for 12-48 hours in an environment of 20-35°C after vacuum packaging. The pressure during curing is 0.6-3 MPa, and it is cured at 45-80°C for 4-12 hours to obtain an in-situ solidified composite solid electrolyte.
[0020] Beneficial effects:
[0021] (1) The preparation method of the present invention is simple. By forming a PLiMA coating layer on the surface of the inorganic nano lithium ion conductor, the release rate of the initiator is controlled, thereby improving the electrochemical performance and cycle performance of the composite electrolyte. At the same time, PLiMA is a lithium-salted acrylic polymer containing lithium ions and can directly provide a lithium ion source. Since PLiMA carries its own lithium ions, it can increase the overall lithium ion concentration and conductivity.
[0022] (2) In the present invention, an initiator is added to the nanostructured inorganic lithium ion conductor. The nanostructured inorganic lithium ion conductor has a high specific surface area and active surface sites, which is helpful for the adsorption and dispersion of the initiator. During the in-situ curing process, the raw materials for preparing the solid electrolyte can be more evenly infiltrated into the battery structure, ensuring the uniform distribution of the solid electrolyte inside the battery, thereby improving the performance and stability of the battery; wherein the structural types of the above-mentioned nano inorganic lithium ion conductor materials specifically include nano elementary materials (nanoparticles, hollow nanospheres, nanosheets, nanowires, nanotubes), nano mesoporous materials and hierarchical micro-nano materials. The PLiMA coating layer can effectively reduce the agglomeration of the inorganic nano lithium ion conductor and enhance its dispersibility in the polymer matrix. At the same time, the PLiMA coating layer can control the release rate of the initiator and avoid the rapid decomposition of the initiator, thereby improving the uniformity and electrochemical performance of the electrolyte.
[0023] (3) In the present invention, the nanostructured inorganic lithium ion conductor has a high specific surface area and active surface sites, which are helpful for the adsorption and dispersion of the initiator. Secondly, this stable carrier can protect the initiator from the influence of the external environment, such as light, oxygen, humidity, etc., and prevent the initiator from slowly decomposing during the preparation process, thereby ensuring the stability and activity of the initiator.
[0024] (4) In the present invention, the nanostructure of the nano inorganic lithium ion conductor material provides a large number of active surface sites, which helps to form more cross-linked structures between the initiator and the polymer matrix. Such cross-linked structures can enhance the mechanical properties and chemical stability of the semi-solid electrolyte and improve the cycle stability and safety of the battery.
[0025] The above description is only an overview of the technical solution of the embodiment of the present application. In order to more clearly understand the technical means of the embodiment of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the embodiment of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used in the specification of the application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0028] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase "embodiments" in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0029] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application is clearly and completely described below.
[0030] The present application provides a composite solid electrolyte prepared based on a nanostructured initiator adsorption carrier. The raw material components for preparing the composite solid electrolyte include, by weight, 20-40 parts of a small molecule polymer monomer, 1-4 parts of an initiator, 2-6 parts of a lithium salt, 3-9 parts of an inorganic nanostructured lithium ion conductor, and 10-20 parts of an organic solvent.
[0031] Embodiment 1:
[0032] The raw material components for preparing the composite solid electrolyte include 20 parts of small molecule polymer monomers, 1 part of initiator, 2 parts of lithium salt, 3 parts of inorganic nanostructured lithium ion conductors and 10 parts of organic solvents in parts by weight.
[0033] In this embodiment, the polymerizable monomers include a combination of acrylic acid, methacrylic acid, and methyl methacrylate.
[0034] In this embodiment, the initiator includes azobisisobutyronitrile and azobisisoheptanenitrile.
[0035] In this embodiment, the lithium salt includes a combination of lithium hexafluorophosphate and lithium tetrafluoroborate.
[0036] In this embodiment, one portion of additive is also included, and the additive includes a combination of vinylene carbonate and fluoroethylene carbonate.
[0037] In this embodiment, the particle size of the inorganic nanostructured lithium ion conductor is 10 nm; the inorganic nanostructured lithium ion conductor includes Li0.5La0.5TiO3.
[0038] In this embodiment, the organic solvent includes a combination of ethylene carbonate and propylene carbonate.
[0039] In this embodiment, a method for preparing a composite solid electrolyte based on a nanostructured initiator adsorption carrier comprises the following steps:
[0040] A. First, dissolve the initiator in a small amount of anhydrous ethanol, stir evenly and add the inorganic nano lithium ion conductor Li 1.3 Al 0.3 Ti 1.7 (PO4)3 powder was ultrasonically dispersed for 30 minutes and then stirred at a low speed for 4 hours to allow the initiator to be uniformly adsorbed on the surface of the inorganic lithium ion conductor;
[0041] B. drying the mixture under vacuum conditions to remove ethanol, thereby obtaining an inorganic lithium ion conductor material adsorbed with an initiator;
[0042] C. Then, PLiMA was dissolved in chloroform at a mass ratio of 1:10, and the inorganic lithium ion conductor adsorbed with the initiator was added to the solution, ultrasonically dispersed for 30 minutes, and stirred at a low speed for 3 hours to ensure that PLiMA was evenly coated on the surface of the inorganic lithium ion conductor;
[0043] D. vacuum drying the mixture to remove chloroform, thereby obtaining an inorganic lithium ion conductor material with PLiMA coated on the surface;
[0044] E. Next, a small molecule polymerization monomer, an initiator, a lithium salt, an organic solvent, and an inorganic lithium ion conductor material coated with PLiMA are mixed in an argon atmosphere glove box to obtain an in-situ solidified electrolyte precursor;
[0045] F. Inject the in-situ curing electrolyte precursor into the battery cell, let it stand for 1 minute under a vacuum of -80 kPa, evacuate and package it, let it stand for 12 hours in an environment of 20°C. The pressure during curing is 0.6 MPa, and cure it at 45°C for 4 hours to obtain an in-situ curing composite solid electrolyte.
[0046] Embodiment 2:
[0047] The raw material components for preparing the composite solid electrolyte include 40 parts of small molecule polymer monomers, 4 parts of initiators, 6 parts of lithium salts, 9 parts of inorganic nanostructured lithium ion conductors and 20 parts of organic solvents in parts by weight.
[0048] In this embodiment, the polymerizable monomer includes a combination of methyl methacrylate and pentaerythritol tetraacrylate.
[0049] In this embodiment, the initiator includes azoisobutylcyanamide and dimethyl azobisisobutyrate.
[0050] In this embodiment, the lithium salt includes a combination of lithium perchlorate and lithium bis(difluorosulfonyl)imide.
[0051] In this embodiment, 3 parts of additives are also included, and the additives include a combination of propylene sulfite and ethylene sulfate.
[0052] In this embodiment, the particle size of the inorganic nanostructured lithium ion conductor is 500 nm; the inorganic nanostructured lithium ion conductor comprises a combination of lithium nitrate and lithium fluoride.
[0053] In this embodiment, the organic solvent includes dimethyl carbonate and diethyl carbonate.
[0054] In this embodiment, a method for preparing a composite solid electrolyte based on a nanostructured initiator adsorption carrier comprises the following steps:
[0055] A. First, dissolve the initiator in a small amount of anhydrous ethanol, stir evenly and add the inorganic nano lithium ion conductor Li1.3 Al 0.3 Ti 1.7 (PO4)3 powder was ultrasonically dispersed for 40 minutes and then stirred at a low speed for 5 hours to allow the initiator to be uniformly adsorbed on the surface of the inorganic lithium ion conductor;
[0056] B. drying the mixture under vacuum conditions to remove ethanol, thereby obtaining an inorganic lithium ion conductor material adsorbed with an initiator;
[0057] C. Then, PLiMA was dissolved in chloroform at a mass ratio of 1:10, and the inorganic lithium ion conductor adsorbed with the initiator was added to the solution, ultrasonically dispersed for 40 minutes, and stirred at a low speed for 4 hours to ensure that PLiMA was evenly coated on the surface of the inorganic lithium ion conductor;
[0058] D. vacuum drying the mixture to remove chloroform, thereby obtaining an inorganic lithium ion conductor material with PLiMA coated on the surface;
[0059] E. Next, a small molecule polymerization monomer, an initiator, a lithium salt, an organic solvent, and an inorganic lithium ion conductor material coated with PLiMA are mixed in an argon atmosphere glove box to obtain an in-situ solidified electrolyte precursor;
[0060] F. Inject the in-situ curing electrolyte precursor into the battery cell, let it stand for 1 minute under a vacuum of -80 kPa, evacuate and package it, and let it stand for 48 hours in a 35°C environment. The pressure during curing is 3 MPa, and it is cured at 80°C for 12 hours to obtain an in-situ curing composite solid electrolyte.
[0061] Embodiment three:
[0062] The raw material components for preparing the composite solid electrolyte include 30 parts of small molecule polymer monomers, 3 parts of initiators, 4 parts of lithium salts, 6 parts of inorganic nanostructured lithium ion conductors and 15 parts of organic solvents in parts by weight.
[0063] In this embodiment, the polymerizable monomer includes a combination of pentaerythritol tetraacrylate and pentaerythritol triacrylate.
[0064] In this embodiment, the initiator includes azoisobutylcyanamide, dimethyl azobisisobutyrate, and dicumyl peroxide.
[0065] In this embodiment, the lithium salt includes a combination of lithium perchlorate, lithium bis(difluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide.
[0066] In this embodiment, 2 parts of additives are also included, and the additives include a combination of vinylene carbonate, fluoroethylene carbonate, and propylene sulfite.
[0067] In this embodiment, the particle size of the inorganic nanostructured lithium ion conductor is 200 nm; the inorganic nanostructured lithium ion conductor comprises a combination of lithium fluoride, trilithium phosphate and lithium niobate.
[0068] In this embodiment, the organic solvent includes a combination of propylene carbonate, dimethyl carbonate, and diethyl carbonate.
[0069] In this embodiment, a method for preparing a composite solid electrolyte based on a nanostructured initiator adsorption carrier comprises the following steps:
[0070] A. First, dissolve the initiator in a small amount of anhydrous ethanol, stir evenly and add the inorganic nano lithium ion conductor Li 1.3 Al 0.3 Ti 1.7 (PO4)3 powder was ultrasonically dispersed for 35 minutes and then stirred at a low speed for 4 hours to allow the initiator to be uniformly adsorbed on the surface of the inorganic lithium ion conductor;
[0071] B. drying the mixture under vacuum conditions to remove ethanol, thereby obtaining an inorganic lithium ion conductor material adsorbed with an initiator;
[0072] C. Then, PLiMA was dissolved in chloroform at a mass ratio of 1:10, and the inorganic lithium ion conductor adsorbed with the initiator was added to the solution, ultrasonically dispersed for 35 minutes, and stirred at a low speed for 4 hours to ensure that PLiMA was evenly coated on the surface of the inorganic lithium ion conductor;
[0073] D. vacuum drying the mixture to remove chloroform, thereby obtaining an inorganic lithium ion conductor material with PLiMA coated on the surface;
[0074] E. Next, a small molecule polymerization monomer, an initiator, a lithium salt, an organic solvent, and an inorganic lithium ion conductor material coated with PLiMA are mixed in an argon atmosphere glove box to obtain an in-situ solidified electrolyte precursor;
[0075] F. Inject the in-situ curing electrolyte precursor into the battery cell, let it stand for 1 minute under a vacuum of -80 kPa, and then let it stand for 36 hours at 30°C after vacuum packaging. The pressure during curing is 2 MPa, and it is cured at 60°C for 8 hours to obtain an in-situ curing composite solid electrolyte.
[0076] Embodiment 4:
[0077] The raw material components for preparing the composite solid electrolyte include 20 parts of small molecule polymer monomers, 4 parts of initiators, 2 parts of lithium salts, 9 parts of inorganic nanostructured lithium ion conductors and 10 parts of organic solvents in parts by weight.
[0078] In this embodiment, the polymerizable monomers include a combination of acrylic acid, methacrylic acid, methyl methacrylate, and pentaerythritol tetraacrylate.
[0079] In this embodiment, the initiator includes azobisisobutyronitrile, azobisisoheptanenitrile, azoisobutylcyanamide, and dimethyl azobisisobutyrate.
[0080] In this embodiment, the lithium salt includes lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(difluorosulfonyl)imide, and lithium bis(trifluoromethyl)sulfonyl imide.
[0081] In this embodiment, 2 parts of additives are also included, and the additives include a combination of vinylene carbonate, fluoroethylene carbonate, propylene sulfite, and ethylene sulfate.
[0082] In this embodiment, the particle size of the inorganic nanostructured lithium ion conductor is 300 nm; the inorganic nanostructured lithium ion conductor comprises a combination of Li0.5La0.5TiO3, lithium nitrate, lithium fluoride, and trilithium phosphate.
[0083] In this embodiment, the organic solvent includes ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and a combination of methyl and ethyl carbonate.
[0084] In this embodiment, a method for preparing a composite solid electrolyte based on a nanostructured initiator adsorption carrier comprises the following steps:
[0085] A. First, dissolve the initiator in a small amount of anhydrous ethanol, stir evenly and add the inorganic nano lithium ion conductor Li 1.3 Al 0.3 Ti 1.7 (PO4)3 powder was ultrasonically dispersed for 30 minutes and then stirred at a low speed for 5 hours to allow the initiator to be uniformly adsorbed on the surface of the inorganic lithium ion conductor;
[0086] B. drying the mixture under vacuum conditions to remove ethanol, thereby obtaining an inorganic lithium ion conductor material adsorbed with an initiator;
[0087] C. Then, PLiMA was dissolved in chloroform at a mass ratio of 1:10, and the inorganic lithium ion conductor adsorbed with the initiator was added to the solution, ultrasonically dispersed for 40 minutes, and stirred at a low speed for 3 hours to ensure that PLiMA was evenly coated on the surface of the inorganic lithium ion conductor;
[0088] D. vacuum drying the mixture to remove chloroform, thereby obtaining an inorganic lithium ion conductor material with PLiMA coated on the surface;
[0089] E. Next, a small molecule polymerization monomer, an initiator, a lithium salt, an organic solvent, and an inorganic lithium ion conductor material coated with PLiMA are mixed in an argon atmosphere glove box to obtain an in-situ solidified electrolyte precursor;
[0090] F. Inject the in-situ solidified electrolyte precursor into the battery cell, let it stand for 1 minute under a vacuum of -80 kPa, evacuate and package it, let it stand for 40 hours in a 32°C environment, the pressure during curing is 2 MPa, and cure it at 65°C for 9 hours to obtain an in-situ solidified composite solid electrolyte.
[0091] Experimental example:
[0092] The composite solid electrolytes prepared in various embodiments of the present invention were used for performance testing, and the data obtained are shown in the following table:
[0093]
[0094] In the present invention, an initiator is added to the nanostructured inorganic lithium ion conductor, and the nanostructured inorganic lithium ion conductor has a high specific surface area and active surface sites, which is helpful for the adsorption and dispersion of the initiator. During the in-situ curing process, the raw materials for preparing the solid electrolyte can be more evenly infiltrated into the battery structure, ensuring the uniform distribution of the solid electrolyte inside the battery, thereby improving the performance and stability of the battery; wherein the structural types of the above-mentioned nano inorganic lithium ion conductor materials specifically include nano elementary materials (nanoparticles, hollow nanospheres, nanosheets, nanowires, nanotubes), nano mesoporous materials and hierarchical micro-nano materials, etc. The PLiMA coating layer can effectively reduce the agglomeration phenomenon of the inorganic nano lithium ion conductor and enhance its dispersibility in the polymer matrix. At the same time, the PLiMA coating layer can control the release rate of the initiator and avoid the rapid decomposition of the initiator, thereby improving the uniformity and electrochemical performance of the electrolyte.
[0095] In the present invention, the nanostructured inorganic lithium ion conductor has a high specific surface area and active surface sites, which are helpful for the adsorption and dispersion of the initiator. Secondly, this stable carrier can protect the initiator from the influence of the external environment, such as light, oxygen, humidity, etc., and prevent the initiator from slowly decomposing during the preparation process, thereby ensuring the stability and activity of the initiator; the nanostructure of the nano inorganic lithium ion conductor material provides a large number of active surface sites, which helps to form more cross-linked structures between the initiator and the polymer matrix. This cross-linked structure can enhance the mechanical properties and chemical stability of the semi-solid electrolyte and improve the cycle stability and safety of the battery.
[0096] The preparation method of the present invention is simple. A PLiMA coating layer is formed on the surface of an inorganic nano lithium ion conductor to control the release rate of the initiator, thereby improving the electrochemical performance and cycle performance of the composite electrolyte. At the same time, PLiMA is a lithium-salted acrylic polymer containing lithium ions and can directly provide a lithium ion source. Since PLiMA carries its own lithium ions, it can increase the overall lithium ion concentration and conductivity.
[0097] As described above, the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.
Claims
1. A composite solid electrolyte prepared by using a nanostructured initiator adsorption carrier, characterized in that: The raw material components for preparing the composite solid electrolyte include 20-40 parts of small molecule polymer monomers, 1-4 parts of initiators, 2-6 parts of lithium salts, 3-9 parts of inorganic nanostructured lithium ion conductors and 10-20 parts of organic solvents in parts by weight.
2. The composite solid electrolyte prepared by a nanostructured initiator adsorption carrier according to claim 1, characterized in that: The polymerizable monomer includes any one of acrylic acid, methacrylic acid, methyl methacrylate, pentaerythritol tetraacrylate, pentaerythritol triacrylate, acrylonitrile, ethylene carbonate, ethylene oxide or 1,3-dioxolane, or a combination of at least two thereof.
3. The composite solid electrolyte prepared by the nanostructured initiator adsorption carrier according to claim 1, characterized in that: The initiator includes any one of azobisisobutyronitrile, azobisisoheptanenitrile, azoisobutylcyanoformamide, dimethyl azobisisobutyrate, dicumyl peroxide or dibenzoyl peroxide, or a combination of at least two thereof.
4. The composite solid electrolyte prepared by the nanostructured initiator adsorption carrier according to claim 1, characterized in that: The lithium salt includes any one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(difluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(oxalato)borate, lithium difluorooxalatoborate or lithium bis(oxalato)borate, or a combination of at least two thereof.
5. The composite solid electrolyte prepared by the nanostructured initiator adsorption carrier according to claim 1, characterized in that: The invention also includes 1 to 3 parts of an additive, wherein the additive includes any one of vinylene carbonate, fluoroethylene carbonate, propylene sulfite, ethylene sulfate, fluorobenzene or sodium dodecyl sulfate, or a combination of at least two of the above.
6. The composite solid electrolyte prepared by the nanostructured initiator adsorption carrier according to claim 1, characterized in that: The particle size of the inorganic nanostructured lithium ion conductor is 10nm-500nm; the inorganic nanostructured lithium ion conductor includes at least one of Li0.5La0.5TiO3, lithium nitrate, lithium fluoride, trilithium phosphate and lithium niobate.
7. The composite solid electrolyte prepared by the nanostructured initiator adsorption carrier according to claim 1, characterized in that: The organic solvent includes any one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl formate, dimethoxymethane or acetonitrile, or a combination of at least two thereof.
8. A method for preparing a composite solid electrolyte based on a nanostructured initiator adsorption carrier, characterized in that: The following steps are involved: A. First, dissolve the initiator in a small amount of anhydrous ethanol, stir evenly and add the inorganic nano lithium ion conductor Li 1.3 Al 0.3 Ti 1.7 (PO4)3 powder, ultrasonically disperse for 30-40 minutes, and then stir at a low speed for 4-5 hours to allow the initiator to be uniformly adsorbed on the surface of the inorganic lithium ion conductor; B. drying the mixture under vacuum conditions to remove ethanol, thereby obtaining an inorganic lithium ion conductor material adsorbed with an initiator; C. Then, PLiMA is dissolved in chloroform at a mass ratio of 1:10, and the inorganic lithium ion conductor adsorbed with the initiator is added to the solution, ultrasonically dispersed for 30-40 minutes, and stirred at a low speed for 3-4 hours to ensure that PLiMA is evenly coated on the surface of the inorganic lithium ion conductor; D. vacuum drying the mixture to remove chloroform, thereby obtaining an inorganic lithium ion conductor material with PLiMA coated on the surface; E. Next, a small molecule polymerization monomer, an initiator, a lithium salt, an organic solvent, and an inorganic lithium ion conductor material coated with PLiMA are mixed in an argon atmosphere glove box to obtain an in-situ solidified electrolyte precursor; F. Inject the in-situ solidified electrolyte precursor into the battery cell, let it stand for 1 minute under a vacuum of -80 kPa, and let it stand for 12-48 hours in an environment of 20-35°C after vacuum packaging. The pressure during curing is 0.6-3 MPa, and it is cured at 45-80°C for 4-12 hours to obtain an in-situ solidified composite solid electrolyte.